Students' Perception on the Mainstream Curriculum in Madrasa Education System: Evidence from Morang and Sunsari Districts, Nepal - Yadav, Raj Kumar; Subedi, Govind (Intellectual Journal of Academic Research, 2025)
Madrasas in Nepal, traditionally focused on Islamic education, have begun incorporating mainstream subjects like Social Studies, Nepali, and English to align with the national education system. This study explores how Madrasa students in Morang and Sunsari districts perceive the mainstream curriculum, focusing on gender and age differences. A cross-sectional survey of Madrasa students in Koshi Province analyzed how gender and age affect views on mainstream subjects and career goals. Gender significantly influences perceptions and career aspirations. Female students (69.31%) value Social Studies, Nepali, and English more for their future careers and mostly aspire to become Madrasa teachers. Male students show more varied career interests. Age does not significantly affect perceptions. The findings suggest the need to reform Madrasa education to address gender-based differences and improve secular education, supporting students' career paths and better integrating Madrasas into Nepal’s national education system.